Testing trade‐offs and the dominance–impoverishment rule among ant communities. (5th July 2020) - Sheard, Julie K.; Nelson, Annika S.; Berggreen, Jeppe D.; Boulay, Raphael; Dunn, Robert R.; Sanders, Nathan J.
Abstract: Aim: Ant communities are believed to be structured by competition, with dominant species competitively excluding subordinates (the dominance–impoverishment rule). However, a high number of seemingly similar species coexist, possibly due to interspecific trade‐offs. Here, we examine the evidence for the dominance–impoverishment rule across a broad latitudinal gradient and explore whether trade‐offs explain coexistence within and among ant communities. Location: 40 sites in 19 countries across Europe, western North America and northern South America. Taxon: Formicidae. Methods: We conducted 2‐hr baiting experiments at each site. Three dominance scores were calculated for each species at each site where it occurred. We then examined the relationship between ant dominance and diversity and tested for the generality of three trade‐offs (dominance–discovery, dominance–thermal tolerance and dominance–generalism) within and among ant communities along with the possible effects of environmental variables on these trade‐offs. Results: We found no support for the dominance–impoverishment rule. Instead, overall species richness at baits was positively correlated with the number of dominant species and exhibited a unimodal relationship with the relative abundance of dominant ants. Moreover, we found little consistent evidence for the three interspecific trade‐offs. Main conclusion: Although total species richness at baits is positively correlated with species richness of dominant species and, to a point, increasing worker numbers of dominants, trade‐offs among species do not appear to shape broad‐scale patterns of coexistence among ants. Species richness declines only when the numbers of dominant workers are very high. Together, these results suggest that while trade‐offs and the dominance–impoverishment rule might promote coexistence or shape ant communities in some locations, the evidence for their being general across communities is scant.